2015
DOI: 10.5603/fm.2015.0051
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of the middle ear in the small Indian mongoose (Herpestes Javanicus)

Abstract: (Folia Morphol 2015; 73, 3: 340-345)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In terms of the cartilage type, epithelial tissue, the presence or absence of glands, the results of the present study were most consistent with the results provided by Kamali et al. ( 2015 ) who studied the nictitating membrane in the small Indian mongoose. The Harderian gland does not exist in all species.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In terms of the cartilage type, epithelial tissue, the presence or absence of glands, the results of the present study were most consistent with the results provided by Kamali et al. ( 2015 ) who studied the nictitating membrane in the small Indian mongoose. The Harderian gland does not exist in all species.…”
Section: Discussionsupporting
confidence: 93%
“…The third eyelid plays a very important role in maintaining the health of the eye surface. It is also capable of protecting the cornea of some predators such as cats from injuries when they move among the vegetation as well as during predation (Kamali et al., 2015 ). The third eyelid in the dromedary has a wide anterior part and its palpebral surface is convex.…”
Section: Introductionmentioning
confidence: 99%
“…The third malleal process (the muscular process, or processus muscularis ) is on the medial surface of the manubrium, and in its median segment, serves as an insertion point for the tensor timpani muscle. Similar features have been reported in most other primates [ 13 , 17 , 19 , 25 ] and Herpetes Javanicus [ 43 ]. In contrast, the tensor tympani muscle seems to be absent in species from Notoryctidae, Chrysochloridae, Tupaiidae, and Ochotonidae, as well as most from the Talpidae , Manidae, and Spalacidae families [ 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…Thanks to its important integrative function, present‐day research for middle ear structure was reported for several species such as the chinese bamboo rat (Pleštilová, Hrouzková, Burda, & Šumbera, 2016), toad (Womack, Stynoski, Voyles, Coloma, & Hoke, 2018), rabbit (Guan et al., 2019), pig (Pracy, White, Mustafa, Smith, & Perry, 1998), miniature pigs (HaiJin et al., 2013), humans, (Arechvo et al., 2013; Isaacson, 2014; Luers & Hüttenbrink, 2016; Sawada, Nara, Fukui, Dodo, & Hirata, 2014; Stieger, Djeric, Kompis, Remonda, & Häusler, 2006; Whyte et al., 2001) other primates, moles (Mason, 2006), dog (Berghes, Parvu, Cucoanes, & Cuca, 2010; Ortug & Türkmenoğlu, 2005), Indian mangoose (Kamali, Gholami, Ahrari‐Khafi, Rasouli, & Shayegh, 2015), horse, cat, cow, rat, mouse (Amin & Tucker, 2006; Blanke, Aupperle, Seeger, Kubick, & Schusser, 2015; Botti, Secci, Ragionieri, Dessole, & Acone, 2006; Mohammadpour, 2010) or other extinct rodents (Lange, Stalleicken, & Burda, 2004), hamster, gerbil, New Zeeland rabbit (Kurtul, Cevik, Bozkurt, & Dursun, 2003), ostrich (Beșoluk et al., 2019; Keenan, Mears, & Skedros, 2017), degu (Argyle & Mason, 2008), weasel or chinchilla (Bergin, Vlajkovic, Bird, & Thorne, 2013; Carrasco, Maass, Dentone, Miranda, & Kukuljan, 2008; Charuta et al., 2011; Hoffstetter et al., 2011; Maier, Tröscher, & Ruf, 2018; Maravilla et al., 2011; Martonos et al., 2019; Rodrigues, Shinohara, Andreo, Buchaim, & Ahmed, 2012; Wang & Gan, 2016).…”
Section: Introductionmentioning
confidence: 99%